Fast Solidification of Pure Gallium at Room Temperature and its Micromechanical Properties. Issue 4 (4th December 2022) - Wang, Xinpeng; Lu, Xueni; Xiao, Wenlong; Liu, Xingtong; Li, Liangtao; Chang, Hao; Yu, Zhenwei; Yang, Xiawei; Chang, Lingqian; Sun, Kang; Wang, Qian; Jiao, Caicai; et al.
Abstract: With excellent electrical conductivity, fluidity, rheological property, and biocompatibility, gallium has been intensively studied in the fields of flexible electronics and devices, thermal management, and soft robotics. However, the large degree of supercooling of gallium presents a large limitation for phase transition‐related applications such as the very low temperature required for solidification, the impurities, and side effects brought in by nucleating agents. In this study, solidification process of liquid gallium by using solid gallium as a nucleating agent is discovered to be fast and facile at room temperature compared with other agent materials including copper, iron, and nickel. Quantificationally, solidified gallium as a nucleating agent, can effectively reduce the supercooling degree from about 66.3 to 14.8 °C. The freezing velocity can reach to 200 mm 3 min −1 . The possible mechanism is reducing the energy barrier via adding nucleation site, allowing rapid solidification at room temperature accompanying heat dissipation. Moreover, micromechanical properties are compared between raw solid Ga and the solidified Ga induced by Ga agent, which suggests a slight decrease in mechanical strength at room temperature with the nucleating agent. It will be beneficial to understand the phase change and also provide guidance for the application of gallium regarding its mechanical properties. Abstract : A unique and facile way for reducing the large degree of supercooling of liquid gallium is put forward. Quantificationally, the freezing velocity is fast, which could reach to 200 mm 3 min −1 . Moreover, micromechanical properties are compared, which will be beneficial to provide guidance for the application of liquid and solidified gallium regarding its mechanical properties.